Analysis of Rapid Turnover Proteins in Chronic Liver Diseases - KUBO, Kiyoshi; HAYASHI, Naoaki; SHINDO, Hiroshi; KUBOI, Hiroshi; TOKUSHIGE, Katsutoshi; YASHIRO, Kurato; KIKUCHI, Hiromi; NAKAJIMA, Taichiro (Japanese Journal of National Medical Services, 1989)
The clinical significance of rapid turnover proteins (RTP) in chronic liver diseases was studied in 10 patients with chronic hepatitis, inactive (CHI), 13 with chronic hepatitis, active (CHA), 19 with compensatory stage liver cirrhosis (LC), 11 with hepatoma accompanied by liver cirrhosis (HCC), and 10 normal subjects. Three kinds of RTP, retinolbinding protein (RBP), prealbumin (PA) and transfferin (Tf), were measured and compared between the groups. In comparison with the normal subjects, RBP was significantly reduced with the pathological progression in all the disease groups. PA also showed almost the same tendency of decrease. When compared with the usual liver function test parameters measured simultaneously, namely, albumin (A1b), hepaplastin test (HT), total bilirubin (TB) and pseudocholinesterase (ChE), both RBP and PA were most closely correlated to A1b. The above findings confirmed that both RBP and PA were helpful not only as nutritional indices but also as indicators of the hepatic reserve. On the other hand, Tf was significantly reduced in only the HCC group and demonstrated an essentially different pattern of behavior from the first-mentioned two proteins. This was considered to be an important finding that suggested the possible metamorphosis of host iron metabolism in association with the development of hepatoma.